2009
DOI: 10.1073/pnas.0903723106
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-mediated changes in hepatic mitochondrial metabolism, structure, and protein levels

Abstract: Leptin reduces body weight in ob/ob mice by decreasing food intake and increasing energy expenditure; however, the mechanisms by which it does the latter are not known. Here we report that 30% of the weight loss induced by leptin treatment of ob/ob mice is due to changes in energy expenditure. In assessing leptin's effects on specific tissues, we found that hepatic basal metabolic rate was paradoxically decreased 1.7-fold with leptin treatment, which was the result of a 1.6-fold reduction in mitochondrial volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
5
36
1
Order By: Relevance
“…For example, during lactation, there is a profound reduction in circulating leptin levels (Kunz et al, 1999;Woodside et al, 2000), which potentially stimulates food intake (Speakman and Król, 2011). In accordance with our results, it has been shown that an increase in leptin levels is associated with reduced mitochondrial volume density and altered substrate oxidation kinetics in liver of mice (Singh et al, 2009). Therefore, it is possible that during lactation the leptin levels cannot be reduced under a specific rate, regardless of the number of pups that can be assigned to a female, explaining why we did not find differences within the reproductive females.…”
Section: Discussionsupporting
confidence: 79%
“…For example, during lactation, there is a profound reduction in circulating leptin levels (Kunz et al, 1999;Woodside et al, 2000), which potentially stimulates food intake (Speakman and Król, 2011). In accordance with our results, it has been shown that an increase in leptin levels is associated with reduced mitochondrial volume density and altered substrate oxidation kinetics in liver of mice (Singh et al, 2009). Therefore, it is possible that during lactation the leptin levels cannot be reduced under a specific rate, regardless of the number of pups that can be assigned to a female, explaining why we did not find differences within the reproductive females.…”
Section: Discussionsupporting
confidence: 79%
“…The regulation of liver metabolism is attributed to the leptin-dependent repression of liver stearoyl-CoA desaturase-1, the rate limiting step in monosaturated fat biosynthesis (28). In addition, recent data indicate that leptin also regulates liver mitochondrial respiratory chain protein expression, mitochondrial function and structure (29), remarkably similar to the previously recognized regulation of mitochondrial function by NO (30,31). Interestingly, delivery of S-nitroso-N-acetylcysteine by gavage to ob/ob mice prevented the development of fatty liver (32).…”
Section: Resultsmentioning
confidence: 99%
“…For example, restricting food intake in ob/ob mice cannot improve lipid metabolism as effectively as leptin treatment. 6,7 In addition, lipodystrophic mice and humans, which have little to no adipose tissue and are hypoleptinemic, also display hyperlipidemia and hepatic steatosis, and these symptoms are ameliorated by leptin. 8,9 Clearly, leptin has effects on lipid metabolism independent of its effects on body weight.…”
mentioning
confidence: 99%
“…Indeed, leptin receptors are found in the liver, 10,11 and leptin administration to ob/ob mice elicits many changes in the expression of genes involved with lipid metabolism in the liver. 6,8,12 Furthermore, leptin treatment in ob/ob mice can reverse hepatic steatosis, 7 potentially due to direct effects of leptin on the liver. 13,14 To address the direct effects of leptin on the liver, Cohen et al 15 knocked out leptin receptors specifically in hepatocytes.…”
mentioning
confidence: 99%